Claudina-3 e Claudina- 4, potenciais marcadores de agressividade no carcinoma endometrial Tipo I - Tonon, Ângela Favorito Santarém [UNESP] (2013)
Carcinoma of the Endometrium is a malignant epithelial tumor which affects pre, peri and post-menopausal women. It is classified into two major groups, according to endocrine, metabolic risk factors and morphological differences: Type I (endometrioid) and Type II (non-endometrioid). Type I accounts for 90% of all endometrial carcinomas and its pathogenesis is linked to excessive estrogen exposure. The Type II is less common, with poorly defined predisposing factors. The most important symptom of endometrial carcinoma is postmenopausal bleeding. Diagnosis is achieved through histological evidence, in association with imaging and laboratorial exams. Treatment is primarily surgical. The most important prognostic factor is the presence or absence of metastases in regional lymph nodes. Bio and tissue markers that indicate worse prognosis are the focus of current research. This study examined the immunoexpression of claudin-3 (CLDN3) and claudin-4 (CLDN4) in endometrial carcinomas Type I and Type II, and their relation to proliferative and atrophic endometrium, clinical and pathological features, hormonal status, proliferation index and p53 expression, in an attempt to establish the importance of these proteins in tumor progression and aggressiveness and their prognostic value. Seventy-nine cases of endometrial carcinoma were studied and compared with 74 normal endometria. The immunoexpression of CLDNs 3 and 4, estrogen receptor, progesterone receptor, cell proliferation index (Ki67) and p53 were all evaluated by immunohistochemistry. Observation verified that the pattern of membrane staining for CLDN3 was diffuse in carcinomas compared with normal endometrium which presented a focal pattern. The number of cells stained with CLDN3 was lower in Type I carcinomas, while staining intensity was greater. Analysis verified that 25% of cases with high expression of CLDN4 and Ki-67 developed metastasis, while 33% of cases with greater CLDN4 staining ...